Assessing miRNAs profile expression as a risk stratification biomarker in oral potentially malignant disorders: A systematic review. (February 2018) - El-Sakka, Haytham; Kujan, Omar; Farah, Camile S.
Highlights: miRNAs are accurately detectable biomarkers in oral potentially malignant disorders. The study design and quality of most studies examining miRNA expression in OPMDs is substandard. Consistent miRNA expression was reported in multiple studies for OLK and OLP. Prognostic or predictive miRNA biomarkers in OPMDs is yet to be established in longitudinal studies. Abstract: Objectives: This paper aims to systematically review current findings on altered expression of miRNAs in OPMDs and whether they can be used as risk stratification biomarkers. Methods: Studies were collated after searching three different electronic databases: PubMed, Embase, Medline. Additional searches were carried out through cross checking the bibliographies of selected articles. After a thorough selection process made by two of the authors, 40 articles met the inclusion criteria and were included in the review. Studies were assessed and analysed in terms of how the candidate miRNA biomarkers were differentially expressed and validated. Results: The included studies examined the expression of miRNAs from human specimens (blood serum/plasma, saliva, tissue) as diagnostic or prognostic biomarkers in patients with OPMDs, some of which have been utilised as risk stratification biomarkers for malignant transformation and have showed promising findings. Conclusion: The current evidence to support or refute the prognostic utility of miRNAs in predicting cancer progression in OPMDs is equivocal. Further longitudinal prospective studies with solid study design are warranted.